An interactive mobile markerless augmented reality for interior design - Nur Dzaqirah, Mohd Tarmidi (2019)
Markerless is one of the techniques in the Augmented Reality system. User does not need to use any marker to produce interactive apps with the 3D model. An Interactive Mobile Markerless Augmented Reality for Interior Design is an application that allows user to decorate their room virtually without using any marker with advance tracking technology and 3D models. 3D models are load from the existing database. It can make user’s task easier to decorate the room because the 3D models and environment is almost same as real life. User can freely decorate the room based on 72 models of furniture with various colour and design. Problems that user generally faced by the people who are busy with their work and have no time to go to various stores to buy furniture for their home. And when they have time for shopping, it is difficult for them to visualize how a particular table or chair will look in a room before it is decorated because could not check for the proper size of the product that fits their room environment. There is difficult to fulfil the customer’s need of decorating their room without imaginary picture to refer. All the problem that user faced can be solve by using this application. The objective of this project is to develop a mobile markerless Augmented Reality application for interior design. Rapid Application Development was chosen as a methodology for this project to ensure the success of the project development. The phases in RAD model consist of Requirements Planning, User Design, Construction, and Cutover. The application was evaluated by the target audience to investigate its effectiveness and user perception towards the application using the User Acceptance Test. The use of the Augmented Reality in this application proves that it can make user’s task easier in order to decorate their room.